2018
DOI: 10.1021/acsomega.8b02541
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanoparticles with a Polymer-Derived Carbon Shell for Improved Lithium-Ion Batteries: Investigation into Volume Expansion, Gas Evolution, and Particle Fracture

Abstract: Silicon (Si) and composites thereof, preferably with carbon (C), show favorable lithium (Li) storage properties at low potential, and thus hold promise for application as anode active materials in the energy storage area. However, the high theoretical specific capacity of Si afforded by the alloying reaction with Li involves many challenges. In this article, we report the preparation of small-size Si particles with a turbostratic carbon shell from a polymer precoated powder material. Galvanostatic charge/disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…A custom setup for highthroughput in situ pressure analysis was demonstrated by Schiele et al [102] and is shown in Figure 12a. In fact, in situ pressure measurements have been performed on some anode and cathode materials in the past [102,103,212,213] (on an electrode level) to gain insights into 3D volume changes of practical electrodes. To probe the "true" gas evolution with cycling, usually the cell volume is determined first.…”
Section: In Situ Gas Analyticsmentioning
confidence: 99%
“…A custom setup for highthroughput in situ pressure analysis was demonstrated by Schiele et al [102] and is shown in Figure 12a. In fact, in situ pressure measurements have been performed on some anode and cathode materials in the past [102,103,212,213] (on an electrode level) to gain insights into 3D volume changes of practical electrodes. To probe the "true" gas evolution with cycling, usually the cell volume is determined first.…”
Section: In Situ Gas Analyticsmentioning
confidence: 99%
“…[52][53][54] Ad etailedd escription of the setup used and the general working principle can be found in Ref. This methodw as already used to monitorL ip lating/stripping and the volume expansion/contraction of graphite and silicon anodes.…”
Section: Pressureanalysismentioning
confidence: 99%
“…This methodw as already used to monitorL ip lating/stripping and the volume expansion/contraction of graphite and silicon anodes. [52][53][54] Ad etailedd escription of the setup used and the general working principle can be found in Ref. [52,54] as well as in Appendix SI 1a nd Figure S4.…”
Section: Pressureanalysismentioning
confidence: 99%
“…The mass increase starting between 500 and 600°C can be assigned to SiO x formation in case of Si nanoparticles. [15] Since this SiO x formation appears in the case of Si/C composites after decomposition of the carbon shell as well, the mass difference at 800°C between both measure-ments is related to the total amount of carbon burnt. The mass increase at a later stage of Si and Si/C nanopowders can be ascribed to the formation of SiO 2 due to oxidation of silicon.…”
Section: Resultsmentioning
confidence: 99%